Accuracy of viscosity regularization models employed by computational fluid dynamics codes - Taglieri Sáo, Yuri [UNESP] (2023)
This work evaluated the accuracy of viscosity regularization models employed by different computational fluid dynamics (CFD) codes in the modeling of viscoplastic flows. Extensive numerical simulations of viscoplastic Hagen–Poiseuille pipe flows were carried out in ANSYS Fluent 20.0, employing both the Herschel–Bulkley–Papanastasiou model and the bi-viscosity model. Three slightly different implementations of the bi-viscosity model were taken into account in the analyses. The numerical results were then compared to the analytical solution of the velocity profile regarding the studied case. While the Herschel–Bulkley–Papanastasiou and the bi-viscosity regularizations employed by OpenFOAM (Tanner and O’Donovan model) and ANSYS Fluent (releases 19.2 onwards) provide satisfactory results, it was observed that the bi-viscosity model employed by previous ANSYS Fluent releases (12.0–19.2) was not adequate to simulate viscoplastic Hagen–Poiseuille flows, indicating that solving more complex flows using such model could yield incorrect results. Although the viscosity regularization model employed by ANSYS Fluent on releases 19.2 onwards has been already corrected, this work recommends CFD users and researchers to be cautious while using outdated releases of the software and consulting scientific works that employed these releases.